Composição química e propriedades de pasta de farinhas de mandioca - Pereira, Bruna Letícia Buzati [UNESP]; Leonel, Magali [UNESP] (EIA Energy in Agriculture, 2013)
This work aimed to analyze the chemical composition and paste properties of cassava flours, from several producers and classifications, marked in different Brazilian cities. Flours were characterized to moisture, ash, fibers, protein, lipids, total sugars and starch. The paste properties were analyzed in RVA. The results showed significant differences to chemical components in cassava flours. The moisture ranged from 4.39 to 10.26, starch (82.19 to 88.90%), ash (0.48 to 1.07%), fiber (3.23 to 6.41%), protein (1.15 to 2.13%), total sugar (0.05 to 0.56%) and lipids (0.40 to 1.24). These differences can be due the variations of raw material and process. The paste properties of flours were different, with viscosity peak ranged from 73.33 to 387.08 RVU, breakdown (2.42 to 248.83RVU, final viscosity (154.92 to 275.5 RVU) and retrogradation tendency (50.75 to 132.5 RVU), showing the influence of kind of processing on flour viscosity.

Este trabalho objetivou caracterizar quanto à composição química e propriedades de pastafarinhas de mandioca de diversas marcas e classificações comercializadas em diferentes localidades. As farinhas foram caracterizadas quanto à: umidade, cinzas, fibras, proteína, matéria graxa, açúcares totais e amido. As propriedades de pasta foram analisadas em viscosímetro RVA. Os resultados mostraram que os produtos de mandioca diferem entre si quanto à composição química, com umidade variando de 4,39 a 10,26%, amido de 82,19 a 88,90%, cinzas de 0,48 a 1,07%, fibras de 3,23 a 6,41, proteína de 1,15 a 2,13%, açúcares totais de 0,05 a 0,56% e matéria graxa de 0,40 a 1,24%, o que pode ser devido a variações nas matérias-primas e processamento. As propriedades de pasta das farinhas mostraram diferenças entre estas para os parâmetros pico de viscosidade (variação de 73,33 a 387,08RVU), quebra de viscosidade (2,42 aa 248,83RVU), viscosidade final (154,92 a 275,50 RVU) e tendência a retrogradação (50,75 a 132,5RVU), evidenciando a influência do tipo de processamento sobre a viscosidade das farinhas.
Chemical composition and pasting properties of cassava flours
Keywords: Product; Nutrients; Viscosity; Manihotesculenta; Produto; Nutrientes; Viscosidade; Manihotesculenta